Single-sided hot-rolled electrostatic cotton and composite filter material and preparation method thereof
By constructing a fluffy-dense asymmetric structure on electrostatic cotton through a single-sided hot rolling process, the problems of insufficient dust holding capacity and rapid increase in resistance of electrostatic cotton are solved, achieving high-efficiency filtration and long service life, simplifying the preparation process and reducing costs.
Patent Information
- Application Number
- CN202611335683.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-11-06
AI Technical Summary
Existing electrostatic cotton has limited dust holding capacity during use, its filtration resistance rises rapidly, and its service life is short. Furthermore, the existing gradient structure filter media has a complex and unstable manufacturing process.
The electret nonwoven substrate is treated by a single-sided hot rolling process to form an asymmetric structure that ranges from fluffy to dense. Combined with a high-efficiency filter layer, the substrate is hot rolled on one side using a pointless light roller. The hot rolling parameters are controlled at 130-145℃, 0.05-0.2MPa, and 6-12m/min to form a dense surface of flat or melt-crosslinked fibers.
It significantly improves dust holding capacity, slows down the rise in filtration resistance, extends service life, and enhances filtration efficiency through the synergistic effect of mechanical interception and electrostatic adsorption, while reducing manufacturing costs and improving the stability of the composite interface.
Smart Images

Figure CN123038579A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to nonwoven filter materials, and more particularly to a single-sided hot-rolled electrostatic cotton, a composite filter material, and a method for preparing the same, suitable for indoor air filtration applications. Background Technology
[0002] Air particulate pollution (such as PM2.5 and PM10) is a significant factor affecting indoor and outdoor environmental quality and human health, impacting various fields including building indoor air purification, industrial dust removal, fresh air systems, and medical protection. Air filter materials prepared using nonwoven technology have become one of the most widely used filter media in these applications due to their advantages such as large specific surface area, adjustable pore structure, flexible molding processes, and low cost.
[0003] Electrostatic cotton is made by storing static charges on the fiber surface of needle-punched nonwoven fabric through electrostatic electret processes (such as corona discharge, triboelectric electret, and water electret). This electrostatic adsorption effect significantly improves the filtration efficiency for submicron and ultrafine particles while maintaining low filtration resistance. However, ordinary electrostatic cotton has a uniform and loose structure, causing particles to accumulate mainly on the dust-facing surface. As filtration time increases, the surface of the electrostatic cotton is quickly covered by particles, leading to a rapid increase in filtration resistance, significantly limiting the dust holding capacity of the filter media, and resulting in a shorter service life.
[0004] Constructing an asymmetric pore structure from coarse to fine pores along the thickness direction of the filter media can guide particulate matter to accumulate in layers within the filter media, thereby significantly improving dust holding capacity and slowing down the increase in resistance. Existing gradient structure filter media usually require the composite of multiple layers of materials with different pore sizes or fiber diameters, which is a relatively complex manufacturing process, and the bonding stability between the multiple layers of materials is challenging, making it difficult to achieve large-scale, low-cost preparation.
[0005] Hot rolling is a mature nonwoven finishing process. It involves applying temperature and pressure to the nonwoven fabric using heated rollers, causing the surface fibers to compress, melt, and bond, thereby altering the material's surface structure and pore distribution. This results in a loose-to-dense asymmetric structure along the thickness direction. Applying single-sided hot rolling to electrostatic cotton allows for a one-step process where the pore size gradually decreases from the unrolled to the rolled surface. The process is simple, requires no additional chemical reagents, and offers significant economic and environmental benefits. Currently, research and application of single-sided hot rolling technology in electrostatic cotton to improve air filtration performance are still in their infancy and require further development. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to improve the dust holding performance of single-layer electrostatic cotton through a single process.
[0007] The first aspect of the present invention provides a single-sided hot-rolled electrostatic cotton for air filtration, comprising an electret nonwoven substrate, wherein the electret nonwoven substrate has one and only one side that has been hot-rolled to form a hot-rolled surface, and the electret nonwoven substrate forms an asymmetric structure along the thickness direction that transitions from a fluffy structure on the unhot-rolled surface to a dense structure on the hot-rolled surface side, wherein the unhot-rolled surface serves as the dust-receiving surface.
[0008] Furthermore, the hot rolling parameters are: hot rolling temperature of 130-145℃, hot rolling linear pressure of 0.05-0.2MPa, and hot rolling speed of 6-12m / min.
[0009] Furthermore, the fibers in the hot-rolled surface are in a flat or melt-crosslinked state, and the pores of the hot-rolled surface are not completely closed.
[0010] Furthermore, the fiber material of the electret nonwoven substrate is selected from one or more of polypropylene, polyester, or core-sheath composite fibers; the electret nonwoven substrate is an electrostatic electret needle-punched nonwoven material.
[0011] A second aspect of the present invention provides a composite filter material, comprising single-sided hot-rolled electrostatic cotton and a high-efficiency filter layer adhered to the hot-rolled surface of the single-sided hot-rolled electrostatic cotton.
[0012] Furthermore, the high-efficiency filter layer is selected from any one of water electret meltblown nonwoven fabric, corona electret meltblown nonwoven fabric, or glass fiber filter paper.
[0013] The third aspect of the present invention provides a method for preparing single-sided hot-rolled electrostatic cotton, wherein electret nonwoven substrate is subjected to single-sided hot rolling treatment by a roller without rolling points.
[0014] Furthermore, the single-sided hot rolling temperature is 140℃, the hot rolling pressure is 0.1MPa, and the hot rolling speed is 10m / min.
[0015] A fourth aspect of the present invention provides a method for preparing a composite filter material, comprising the following steps: S1: Single-sided hot-rolled electrostatic cotton is obtained by hot-rolling electret nonwoven substrate on one side using a light roller without rolling points. S2, the hot-rolled surface of the single-sided hot-rolled electrostatic cotton in step 1 is combined with the high-efficiency filter layer.
[0016] Furthermore, in step 1, the hot rolling temperature is 140℃, the hot rolling pressure is 0.05 MPa, and the hot rolling speed is 10 m / min.
[0017] The present invention has the following beneficial effects: 1. The loose-dense porous structure significantly improves dust holding capacity and slows down the increase in resistance. This invention utilizes a single-sided hot-rolling process to construct an asymmetric microstructure in the thickness direction of the electret nonwoven substrate, where the bulkiness decreases from the unrolled to the hot-rolled side. This results in a three-dimensional, hierarchical accumulation of particulate matter within the filter media. Compared to traditional uniform filter media that are prone to forming filter cakes in localized areas, the single-sided hot-rolling process significantly increases the dust holding capacity of a single layer of electrostatic cotton, effectively slowing down the sharp increase in filtration resistance and extending the service life of the filter media. Further multi-airflow tests demonstrate that the dust holding capacity of the composite material, combining single-sided hot-rolled electrostatic cotton with water-electret meltblown fabric, is higher than that of the unrolled composite filter media at equivalent test airflow rates of 60, 85, 120, and 180 L / min.
[0018] 2. The efficient synergy between physical interception and electrostatic adsorption balances high protection with low resistance. The needle-punched electrostatic cotton substrate selected in this invention carries abundant electrostatic charges on its interior and fiber surface. The single-sided hot rolling process flattens the surface fibers to form a dense surface while preserving the high bulk of the material. Furthermore, within the parameters of hot rolling temperature (130-145℃), hot rolling pressure (0.05-0.2MPa), and hot rolling speed (6-12m / min), the overall electrostatic field effect is not severely disrupted. Submicron and fine particles are electrostatically adsorbed during penetration, achieving a synergistic effect of mechanical filtration and electrostatic properties.
[0019] 3. A one-step method for constructing loose-dense porous structures is simple and produces structures with high stability. Compared to traditional gradient structure filter media, which heavily rely on multi-layer composite materials of different materials, involve complex processes, and are prone to interlayer delamination and structural instability, this invention only requires a hot rolling device with a single-sided heated, pointless smooth roller to construct a stable gradient structure on a single layer of material in a single step. This forming process not only reduces manufacturing costs but also endows the composite interface with high structural stability.
[0020] 4. It has a wide range of applications and outstanding comprehensive economic and environmental benefits. The single-sided hot-rolled electrostatic cotton and its composite filter material prepared by this invention can be widely used in various scenarios such as building fresh air systems, air purifiers, and industrial dust removal, and can adapt to dust loading conditions under different filtration air volumes. Its significantly improved dust holding capacity and long service life can reduce the frequency of filter element replacement and reduce waste generation, showing good prospects in terms of economic value and environmental benefits. Attached Figure Description
[0021] Figure 1 This is a scanning electron microscope (SEM) structural diagram of a single-sided hot-rolled electrostatic cotton disclosed in this invention.
[0022] Figure 2 This is a schematic diagram comparing the initial filtration efficiency of electrostatic cotton before and after hot rolling, as disclosed in this invention.
[0023] Figure 3 This is a schematic diagram of the stacking of single-sided hot-rolled electrostatic cotton particles according to the present invention.
[0024] Figure 4 This is a schematic diagram of the stacked structure of the composite air filter material disclosed in this invention.
[0025] Figure 5 The graph shows the change in filtration resistance over time in the dust holding capacity test for Examples 1-10.
[0026] Figure 6 The graph shows the change in filtration resistance over time in the dust holding capacity test for Examples 11-20.
[0027] Figure 7 For Comparative Example 2, Example 13 shows the filter resistance versus time curves at equivalent test air volumes of 60, 85, 120, and 180 L / min.
[0028] Figure 8 For Comparative Example 2, Example 13 shows a comparison of dust holding capacity under different equivalent test air volumes. Detailed Implementation
[0029] The present invention will now be described in further detail with reference to the accompanying drawings and data. It should be understood that the embodiments are merely illustrative of the invention and are not intended to limit the scope of the invention in any way.
[0030] The following are the test methods for relevant performance indicators in each embodiment and comparative example, as well as the specific procedures of related experiments: Thickness testing: Referencing national standard GB / T 24218.2-2009, a fabric thickness gauge YD141D-II was used. The sample was placed under standard atmospheric conditions of 20±2℃ and 65±4% relative humidity for at least 24 hours for conditioning. The thickness gauge was then turned on and calibrated. The test pressure was set to 0.5 kPa (or the reference pressure adjusted according to the specific weight of the nonwoven fabric), and the presser foot area was 25 cm². 2 Place the conditioned sample flat between the reference plate and the pressure foot, slowly lower the pressure foot to apply pressure, hold for 10 seconds, and then read the thickness value from the instrument. Randomly cut 10 test samples from different parts of each sample to be tested and repeat the test. After removing outliers, take the arithmetic mean, accurate to 0.01 mm.
[0031] Dust Holding Capacity Test: Referring to national standard GB / T 14295-2019, the Jiaxing Longman LM-779-I filter material dust holding capacity performance test bench was used. Test Procedure: ① Sample Preparation and Initial Weighing: The cut electrostatic cotton sample (or composite filter material sample) was weighed on a precision electronic balance, and the initial mass M1 (accurate to 0.1 mg) was recorded. ② Sample Installation and Airflow Setting: The weighed sample was flatly clamped in the filter material fixture of the test bench, with an effective test area of 100 cm². 2 Note: For the single-sided hot-rolled electrostatic cotton of this invention, the unrolled surface retaining its original fluffy morphology must face upstream of the airflow as the dust-facing surface, while the dense hot-rolled surface faces downstream of the airflow; for composite materials, ensure that the airflow passes sequentially through the unrolled surface of the electrostatic cotton, the hot-rolled surface of the electrostatic cotton, and the water electret meltblown fabric layer. Set the test airflow rate to 85 L / min. ③ Dust loading: Start the dust generator and inject standard test dust into the airflow, controlling the test dust concentration to be constant at 1 g / m³. 3 Dust-laden air continuously passes through the sample, and the instrument records the dynamic changes in filtration time, filtration efficiency, and filtration resistance in real time. ④ Termination judgment and dust holding capacity calculation: Filtration loading continues, and when the filtration resistance of the sample reaches the preset termination condition (in this invention, for pure single-sided hot-rolled electrostatic cotton samples, the termination condition is set to an increase in resistance of 100 Pa; for electrostatic cotton and water electret meltblown fabric composite materials, the termination condition is set to an increase in resistance of 200 Pa), dust generation and air extraction are immediately stopped. The sample is carefully removed, weighed again using a precision balance, and the mass M2 after loading is recorded. ⑤ Data processing: The test results are characterized by the dust holding capacity per unit area D, and the calculation formula is D=(M2-M1) / A, where A is the effective test area (m²), and the unit is g / m².
[0032] Dust Holding Capacity Test under Different Airflow Conditions: The equivalent surface velocity method was used to test the dust holding capacity of composite filter media under different airflow conditions. The effective test area was uniformly set to 50 cm², and the actual airflow of the equipment was set to 30, 42.5, 60, and 90 L / min, corresponding to equivalent test airflow of 60, 85, 120, and 180 L / min for a test area of 100 cm². The dust concentration for each test condition was maintained at 1 g / m³. The dust-laden airflow passed sequentially through the unheated surface of electrostatic cotton, the heat-rolled surface of electrostatic cotton, and the water-electret meltblown fabric. The initial filtration resistance P0 under the corresponding condition was recorded at the start of the test, and loading was terminated when the filtration resistance reached 3.6 times the initial filtration resistance. Each test was conducted in parallel three times. The dust holding capacity was calculated by dividing the difference in sample mass before and after loading by the effective filtration area, in g / m².
[0033] like Figure 3As shown, this invention discloses a single-sided hot-rolled electrostatic cotton for air filtration, comprising an electret nonwoven substrate. The electret nonwoven substrate has only one side that has been hot-rolled to form a hot-rolled surface. The bulkiness of the electret nonwoven substrate decreases from the unhot-rolled surface towards the hot-rolled surface, with the unhot-rolled surface serving as the dust-attracting surface. It should be emphasized that the bulkiness of the electret nonwoven substrate from the unhot-rolled surface towards the hot-rolled surface is not a gradient decrease; that is, the electret nonwoven substrate forms an asymmetric structure along its thickness, transitioning from a bulky structure on the unhot-rolled surface to a dense structure on the hot-rolled surface. The asymmetric structure refers to the fact that the unhot-rolled surface and the main body of the single-sided hot-rolled electrostatic cotton are bulky dust-attracting surfaces with their original fiber morphology, while the hot-rolled surface is a dense surface where the fibers partially melt and bond together. The interior and fiber surface of the electret nonwoven substrate carry electrostatic charges. The bulky dust-attracting surface acts on large dust particles through electrostatic attraction and mechanical interception, while the dense surface intercepts fine particles that penetrate deeper.
[0034] The parameters for hot rolling are: hot rolling temperature of 130-145℃, hot rolling linear pressure of 0.05-0.2MPa, and hot rolling speed of 6-12m / min. For example... Figure 1 As shown, the fibers in the hot-rolled surface are in a flat or melt-crosslinked state, and the pores of the hot-rolled surface are not completely closed. The fiber material of the electret nonwoven substrate is selected from one or more of polypropylene, polyester, or core-sheath composite (ES) fibers; the forming process of the electret nonwoven substrate is needle punching.
[0035] like Figure 4 As shown, this invention also discloses a composite filter material, comprising single-sided hot-rolled electrostatic cotton and a high-efficiency filter layer adhered to the hot-rolled surface of the single-sided hot-rolled electrostatic cotton. Dust-laden airflow sequentially passes through the fluffy dust-receiving surface, the dense surface, and the high-efficiency filter layer. The high-efficiency filter layer is selected from any one of water-electret meltblown nonwoven fabric, corona-electret meltblown nonwoven fabric, or glass fiber filter paper.
[0036] This invention also discloses a method for preparing single-sided hot-rolled electrostatic cotton, comprising the following steps: S1. A hot rolling equipment with a single-sided heated, pointless light roller is used to perform surface heat treatment on the fluffy electret nonwoven substrate; S2. Control the temperature of the heated roller to be near the polymer melting point, so that the fibers on the contact side partially melt and are flattened to form a dense surface; S3. The side that does not contact the heated roller does not melt and close the pores, maintaining its original fluffy shape and forming a fluffy dust-facing surface.
[0037] The hot rolling temperature for single-sided hot rolling is 130-145℃, the hot rolling pressure is 0.05-0.2MPa, and the hot rolling speed is 6-12m / min. In one embodiment, the single-sided hot rolling temperature is 140℃, the hot rolling pressure is 0.1MPa, and the hot rolling speed is 10m / min.
[0038] Among them, a smooth roller without creases is selected as the hot press roller to avoid the formation of a closed film that would cause a sharp increase in filtration resistance. After hot rolling, the fiber pile on the hot-rolled side is flattened and slightly melted and bonded to form a thin and dense fiber network; the fiber morphology on the un-hot-rolled side retains the fluffy and porous characteristics of the original needle-punched fabric, contributing less to airflow resistance.
[0039] Considering the risk of significant escape of the electrostatic charge carried by the electrostatic cotton under the thermal effects of hot rolling, which would lead to a substantial decrease in its filtration performance, the initial filtration efficiency of the electrostatic cotton before and after hot rolling was tested at an airflow rate of 85 L / min. Figure 2 The results showed that within the range of hot rolling temperature (130–145℃), hot rolling pressure (0.05–0.2 MPa), and hot rolling speed (6–12 m / min), the initial filtration efficiency of the electrostatic cotton did not change significantly before and after single-sided hot rolling.
[0040] This invention also discloses a method for preparing a composite filter material, comprising the following steps: S1: Single-sided hot-rolled electrostatic cotton is obtained by hot-rolling electret nonwoven substrate on one side using a light roller without rolling points. S2, the hot-rolled surface of the single-sided hot-rolled electrostatic cotton in step 1 is combined with the high-efficiency filter layer.
[0041] In one embodiment, in step 1, the hot rolling temperature is 140°C, the hot rolling pressure is 0.05 MPa, and the hot rolling speed is 10 m / min.
[0042] Comparative Example 1 Comparative Example 1 is raw electrostatic cotton without any heat-rolling treatment. Both sides of the un-heat-rolled electrostatic cotton retain the fluffy and porous morphology of needle-punched fabric, without a thickness-direction gradient pore structure.
[0043] The preparation steps of the electrostatic cotton in Comparative Example 1 are as follows: Step 1: Raw material preparation. Select electrostatic electret needle-punched PP nonwoven fabric with an areal density of 178±5.6g / m² and a thickness of 3.41±0.16mm.
[0044] Step 2: Cut the selected electrostatic cotton into 15cm×15cm samples. Using any side as the dust-facing side, conduct a dust holding capacity test using the Jiaxing Longman LM-779-I filter material dust holding capacity performance testing bench (test termination condition: resistance increase of 100Pa). Test results: Dust holding capacity is 126.85±1.66g / m³.2 .
[0045] Comparative Example 1 shows that the unheat-rolled electrostatic cotton has a uniform and fluffy structure, with particles accumulating only on the dust-facing surface. As a result, its dust holding capacity is limited when the termination resistance is reached, and its service life is relatively short.
[0046] Example 1 In this embodiment, under the conditions of fixed hot rolling pressure of 0.1 MPa and hot rolling speed of 10 m / min, single-sided hot-rolled electrostatic cotton with a hot rolling temperature of 130℃ (sample 130-0.1-10) was prepared to investigate the effect of hot rolling temperature on the dust holding capacity of a single layer.
[0047] The specific steps are as follows: Step 1: Raw material preparation. Select electrostatic electret needle-punched PP nonwoven fabric with an areal density of 178±5.6g / m² and a thickness of 3.41±0.16mm.
[0048] Step 2: Single-sided hot rolling treatment. With a fixed hot rolling pressure of 0.1 MPa, a hot rolling speed of 10 m / min, and a hot rolling roll temperature of 130℃, the electrostatic cotton was fed into the hot rolling device with a smooth roll without rolling points one by one for treatment. The hot-rolled side was in contact with the hot roll, while the unrolled side maintained its fluffy morphology, resulting in sample 130-0.1-10.
[0049] Example 2 The difference between this embodiment and Embodiment 1 is that in the second step, the temperature of the hot rolling roll is set to 135°C, and sample 135-0.1-10 is obtained.
[0050] Example 3 The difference between this embodiment and Embodiment 1 is that in the second step, the temperature of the hot rolling roll is set to 140°C, and sample 140-0.1-10 is obtained.
[0051] Example 4 The difference between this embodiment and Embodiment 1 is that in the second step, the temperature of the hot rolling roll is set to 145°C, and sample 145-0.1-10 is obtained.
[0052] Single-layer performance tests were conducted on Examples 1-4: The samples from each embodiment were cut into 15cm × 15cm specimens, with the unrolled side as the dust-facing side. Dust holding capacity tests were conducted using the Jiaxing Longman LM-779-I filter material dust holding capacity performance testing bench (dust concentration 1g / m³, test airflow 85L / min, termination condition: resistance increase of 100Pa). The test results are shown in the table below: Table 1 Test results show that, under fixed pressure of 0.1 MPa and speed of 10 m / min, the dust holding capacity of a single layer of electrostatic cotton is 140.31 ± 3.63 g / m³ when the hot rolling temperature is 135℃. 2 The dust holding capacity was 10.61% higher than that of unrolled material; the highest dust holding capacity (141.59±9.65g / m³) was achieved when the hot rolling temperature was 140℃. 2 The efficiency was 11.62% higher than that of unrolled fibers. Below 135℃, the surface heat melting was insufficient, resulting in limited densification of the hot-rolled surface and an indistinct gradient pore structure. At 145℃, the fibers were heated excessively, leading to overly dense hot-rolled layers. This reduced the overall pore space and may have caused some damage to the fiber structure, thus decreasing the dust-holding capacity improvement. Therefore, the optimal hot-rolling temperature for single-layer use is 140℃.
[0053] Example 5 The difference between this embodiment and Embodiment 2 is that in the second step, the hot rolling pressure is fixed at 0.05 MPa, and sample 135-0.05-10 is obtained.
[0054] Example 6 The difference between this embodiment and Embodiment 2 is that in the second step, the hot rolling pressure is fixed at 0.15 MPa, and sample 135-0.15-10 is obtained.
[0055] Example 7 The difference between this embodiment and Embodiment 2 is that in the second step, the hot rolling pressure is fixed at 0.2 MPa, and sample 135-0.2-10 is obtained.
[0056] Single-layer performance tests were conducted on Examples 2, 5-7: The samples from each embodiment were cut into 15cm × 15cm specimens, with the unrolled side as the dust-facing side. Dust holding capacity tests were conducted using the Jiaxing Longman LM-779-I filter material dust holding capacity performance testing bench (dust concentration 1g / m³, test airflow 85L / min, termination condition: resistance increase of 100Pa). The test results are shown in the table below: Table 2 Test results show that, under fixed temperature of 135℃ and speed of 10m / min, the single-layer electrostatic cotton has the highest dust holding capacity when the hot rolling pressure is 0.1MPa. At a pressure of 0.05MPa, the densification degree of the hot-rolled surface is lower, the gradient pore structure is not fully formed, and the increase in dust holding capacity (+3.79%) is lower than that of the 0.1MPa group (+10.61%). When the pressure is greater than or equal to 0.15MPa, the compression effect of the rolls on the overall material is significantly enhanced, the overall thickness of the filter material is excessively compressed, the pore space is greatly reduced, and the dust holding capacity decreases instead of increasing (-2.38% and -10.31%). Therefore, the optimal hot rolling pressure for single-layer use is 0.1MPa.
[0057] Example 8 The difference between this embodiment and Embodiment 2 is that in the second step, the hot rolling speed is 6 m / min, and sample 135-0.1-6 is obtained.
[0058] Example 9 The difference between this embodiment and Embodiment 2 is that in the second step, the hot rolling speed is 8 m / min, and sample 135-0.1-8 is obtained.
[0059] Example 10 The difference between this embodiment and Embodiment 2 is that in the second step, the hot rolling speed is 12 m / min, and sample 135-0.1-12 is obtained.
[0060] Single-layer performance tests were conducted on Examples 2, 8-10: The samples from each embodiment were cut into 15cm × 15cm specimens, with the unrolled side as the dust-facing side. Dust holding capacity tests were conducted using the Jiaxing Longman LM-779-I filter material dust holding capacity performance testing bench (dust concentration 1g / m³, test airflow 85L / min, termination condition: resistance increase of 100Pa). The test results are shown in the table below: Table 3 Test results show that, under fixed temperature conditions of 135℃ and pressure of 0.1MPa, the highest dust holding capacity (140.31±3.63g / m³) is achieved at a hot rolling speed of 10m / min. 2 At a speed of 8 m / min, the fiber heating time was relatively long, resulting in slightly excessive fiber melting on the hot-rolled surface and a denser hot-rolled layer. The increase in dust holding capacity (+3.3%) was lower than that of the 10 m / min group. The dust holding capacity at a speed of 6 m / min was even slightly lower than that of the un-hot-rolled group, presumably due to the longer hot-rolling time at this speed leading to a sharp decrease in thickness. At a speed of 12 m / min, the heating time was too short, resulting in insufficient densification of the hot-rolled surface and a slightly weaker effect on increasing dust holding capacity.
[0061] Based on Examples 1-10, the optimal hot-rolling parameters for single-layer, single-sided hot-rolled electrostatic cotton are 140℃ - 0.1MPa - 10m / min, resulting in a dust holding capacity increase of approximately 11.62% compared to un-hot-rolled cotton. See the curves showing the filtration resistance versus time for each group. Figure 5 .
[0062] Comparative Example 2 One side of the raw electrostatic cotton without any heat-rolling treatment is laminated with water-electret meltblown fabric. Both sides of the unheat-rolled electrostatic cotton retain the loose and porous morphology of needle-punched fabric, without a thickness gradient pore structure.
[0063] The preparation steps of the electrostatic cotton composite filter material in the comparative example are as follows: Step 1: Raw material preparation. Select electrostatic electret needle-punched PP nonwoven fabric with an areal density of 178±5.6 g / m² and a thickness of 3.41±0.16 mm. Select water electret meltblown fabric with an areal density of 43.45±1.09 g / m², a thickness of 0.44±0.02 mm, and a filtration efficiency of 99.92±0.009% (32 L / min).
[0064] Step 2: Lay down any side of the original electrostatic cotton that has not undergone any hot rolling treatment with water electret meltblown cloth, and then cut the electrostatic cotton-water electret meltblown cloth composite filter material into 15cm×15cm samples, with the side of the electrostatic cotton that is not attached to the water electret meltblown cloth as the dust-facing side.
[0065] Dust holding capacity was tested using the Jiaxing Longman LM-779-I filter media dust holding capacity performance testing bench (test termination condition: resistance increase of 200 Pa). Test results: Dust holding capacity was 191.42 ± 4.76 g / m³. 2 .
[0066] Example 11 Under the conditions of fixed hot rolling pressure of 0.05 MPa and hot rolling speed of 10 m / min, single-sided hot-rolled electrostatic cotton with a hot rolling temperature of 120℃ was prepared. The single-sided hot-rolled electrostatic cotton was then combined with water electret meltblown cloth and a dust holding capacity test was conducted to investigate the effect of hot rolling temperature on the dust holding capacity of the composite filter material.
[0067] The preparation steps for each sample are as follows: Step 1: Raw material preparation. Select electrostatic electret needle-punched PP nonwoven fabric with an areal density of 178±5.6 g / m² and a thickness of 3.41±0.16 mm. Select water electret meltblown fabric with an areal density of 43.45±1.09 g / m², a thickness of 0.44±0.02 mm, and a filtration efficiency of 99.92±0.009% (32 L / min).
[0068] Step 2: Single-sided hot rolling treatment. With a fixed hot rolling pressure of 0.05MPa, a hot rolling speed of 10m / min, and a hot rolling roll temperature of 120℃, the electrostatic cotton is fed into the single-sided hot rolling device without rolling points for treatment one group at a time. The hot-rolled side contacts the hot roll, while the unrolled side retains its fluffy shape.
[0069] Step 3: Lay the hot-rolled surface of each single-sided hot-rolled electrostatic cotton with water electret meltblown cloth, and then cut the single-sided hot-rolled electrostatic cotton-water electret meltblown cloth composite filter material into 15cm×15cm samples to obtain sample 120-0.05-10+water electret meltblown cloth.
[0070] Example 12 The difference between this embodiment and Embodiment 11 is that in the second step, the hot rolling temperature is set to 130℃ to obtain sample 130-0.05-10+water electret meltblown fabric.
[0071] Example 13 The difference between this embodiment and Embodiment 11 is that in the second step, the hot rolling temperature is set to 140℃ to obtain sample 140-0.05-10+water electret meltblown fabric.
[0072] Example 14 The difference between this embodiment and Embodiment 11 is that in the second step, the hot rolling temperature is set to 150℃ to obtain sample 150-0.05-10+water electret meltblown fabric.
[0073] Dust holding capacity tests were conducted on Examples 11-14: Using the unheat-rolled surface of electrostatic cotton as the dust-facing surface, a dust holding capacity test was conducted (dust concentration 1 g / m³, test airflow 85 L / min, termination condition: resistance increase of 200 Pa). The dust-laden airflow sequentially passed through the unheat-rolled surface, the heat-rolled surface, and the water-electret meltblown fabric (e.g., Figure 4 (As shown). The test results are shown in the table below: Table 4 Test results show that when used in combination with water-electret meltblown fabric, the optimal hot rolling temperature is 140℃ (dust holding capacity 220.11±3.16g / m³). 2 Compared to non-hot-rolled composite filter media, the dust holding capacity is improved by 14.99%. The temperature is consistent with the group with the highest average dust holding capacity in single-layer temperature screening; the optimal pressure in the composite scenario is 0.05 MPa, lower than 0.1 MPa in single-layer pressure screening. After composite processing, the downstream meltblown fabric undertakes the precise interception of fine particles, while the electrostatic cotton mainly undertakes the interception and containment of large particles. Under lower pressure, a moderately dense and relatively thin hot-rolled layer is formed through thermal action at 140℃, which both preserves the overall dust holding space and helps maintain the structural stability of the electrostatic cotton after capturing large particles. Dust holding capacity at 150℃ (216.68±7.05 g / m³).2 The group slightly below 140℃ is presumably due to excessively high temperatures causing excessive blockage of the hot-rolled surface, reducing the amount of fine particles penetrating into the meltblown fabric, and affecting the overall dust holding efficiency.
[0074] Example 15 The difference between this embodiment and embodiment 13 is that in the second step, the hot rolling pressure is fixed at 0.1 MPa to obtain sample 140-0.05-10+water electret meltblown fabric.
[0075] Example 16 The difference between this embodiment and embodiment 13 is that in the second step, the hot rolling pressure is fixed at 0.15 MPa to obtain sample 140-0.05-10+water electret meltblown fabric.
[0076] Example 17 The difference between this embodiment and embodiment 13 is that in the second step, the hot rolling pressure is fixed at 0.2 MPa to obtain sample 140-0.05-10+water electret meltblown fabric.
[0077] Dust holding capacity tests were conducted on Examples 13, 15-17. Using the unheat-rolled surface of electrostatic cotton as the dust-facing surface, a dust holding capacity test was conducted (dust concentration 1 g / m³, test airflow 85 L / min, termination condition: resistance increase of 200 Pa). The dust-laden airflow passed sequentially through the unheat-rolled surface, the heat-rolled surface, and the water-electret meltblown fabric. The test results are shown in the table below: Table 5 Test results show that in composite application scenarios, the optimal hot-rolling pressure decreases to 0.05 MPa (dust holding capacity 220.11 ± 3.16 g / m², an increase of 14.99%), lower than the optimal pressure for single-layer application (0.1 MPa). This is consistent with the aforementioned mechanism analysis: the composite electrostatic cotton primarily functions to accommodate large particles, requiring a more porous overall pore space. Low pressure can reduce compression of the overall structure while forming a thin hot-rolled layer, thus preserving as much dust-holding space as possible. In the groups with pressures of 0.15 MPa and 0.2 MPa, the effective dust-holding space is reduced due to excessive compression of the overall structure, resulting in a significantly lower increase in the dust holding capacity of the composite filter material.
[0078] Example 18 The difference between this embodiment and embodiment 13 is that in the second step, the hot rolling speed is 2m / min, and sample 140-0.05-2+water electret meltblown fabric is obtained.
[0079] Example 19 The difference between this embodiment and embodiment 13 is that in the second step, the hot rolling speed is 6 m / min, and sample 140-0.05-6+water electret meltblown fabric is obtained.
[0080] Example 20 The difference between this embodiment and embodiment 13 is that in the second step, the hot rolling speed is 14 m / min, and sample 140-0.05-14+water electret meltblown fabric is obtained.
[0081] Dust holding tests were conducted on Examples 13, 18-20, using the unheated surface of the electrostatic cotton as the dust-facing surface. The dust concentration was 1 g / m³, the test airflow was 85 L / min, and the termination condition was a resistance increase of 200 Pa. The dust-laden airflow sequentially passed through the unheated surface, the heat-rolled surface, and the water-electret meltblown fabric. The test results are shown in the table below: Table 6 Test results show that, under combined usage scenarios, the group with a hot rolling speed of 10 m / min has the highest dust holding capacity (220.11 ± 3.16 g / m). 2 Compared to the unheated composite filter material, the filtration resistance increased by 14.99%. Higher speed means shorter fiber heating time, resulting in rapid melting of the fibers on the hot-rolled surface and the formation of a thinner hot-rolled layer, preserving more dust-holding space. The group with a speed of 2 m / min (-3.7%) performed poorly, suggesting that the hot-rolling effect was more pronounced under this speed and temperature / pressure combination. The groups with speeds of 6 m / min and 14 m / min both showed some improvement, but less than the 10 m / min group. Considering the overall speed test results, a hot-rolling speed of 10 m / min is more conducive to forming an ideal thin hot-rolled layer in composite applications. The filtration resistance change curves of each group over time are shown below. Figure 6 As shown.
[0082] Comparative Example 2 and Example 13 were tested for dust holding capacity at various air volumes. Two types of composite filter media were cut and clamped in a fixture with an effective test area of 50 cm². The actual airflow of the equipment was set to 30, 42.5, 60, and 90 L / min, corresponding to equivalent test airflows of 60, 85, 120, and 180 L / min for a test area of 100 cm². The dust concentration was maintained at 1 g / m³. The initial filtration resistance P0 was measured first for each operating condition, and loading was terminated when the filtration resistance reached 3.6P0. Each group was tested in parallel three times, and the obtained filtration resistance curves are shown in [Figure number missing]. Figure 7 The test results are shown in the table below.
[0083] Table 7 From Table 7 and Figure 8 It is evident that as the equivalent test air volume increases from 60 L / min to 180 L / min, the dust holding capacity of both types of composite filter materials shows a monotonic upward trend. Meanwhile, Figure 7The filter resistance curve shown shifts towards a shorter time as the air volume increases, indicating that a higher air volume increases the amount of dust reaching the filter material per unit time, and accelerates the processes of pore filling, particle bridging, and surface dust layer formation within the filter material.
[0084] Under the same equivalent test air volume, the dust holding capacity of the hot-rolled composite filter material was higher than that of the non-hot-rolled composite filter material, and its filtration resistance curve was generally delayed. This indicates that the loose-dense gradient structure formed by single-sided hot rolling can allow particulate matter to be deposited stepwise along the thickness direction of the electrostatic cotton, reducing the concentrated clogging of dust at the water electret meltblown fabric and composite interface, and improving the utilization rate of the dust storage space inside the electrostatic cotton. As the air volume increases, the time for both types of filter materials to enter the surface filtration stage is shortened, and the time difference between the two gradually decreases. This is because the high air volume accelerates the entire dust loading process, and the additional dust storage space provided by the hot-rolled structure is utilized in a shorter time. At the same time, the effects of near-surface deposition and dust layer filtration gradually increase.
[0085] The improvement in dust holding capacity of hot-rolled composite filter media compared to unhot-rolled composite filter media initially increases and then decreases with increasing airflow. At 60 L / min, the loose pores of the unhot-rolled needled layer can effectively utilize deep dust storage, thus the relative advantage of the hot-rolled structure is relatively small. When the airflow increases to 85-120 L / min, the tendency for dust to concentrate and deposit in the melt-blown layer and composite interface of the unhot-rolled filter media strengthens, while the hot-rolled filter media can still achieve graded interception and load sharing through gradient pores, with its improvement reaching a maximum of 15.75% at 120 L / min. When the airflow further increases to 180 L / min, both types of filter media quickly transition to near-surface deposition and dust layer resistance as the dominant factors, and the relative advantage of the hot-rolled gradient structure weakens, but its dust holding capacity is still 10.32% higher than that of the unhot-rolled composite filter media. These results indicate that the composite filter material of this invention has a stable dust holding capacity improvement effect within the equivalent test airflow range of 60-180 L / min.
[0086] The experimental results from the above embodiments show that: When used in a single layer, the effect of single-sided hot rolling on the dust holding capacity of electrostatic cotton varies with process parameters. Some parameter combinations show an increase, while others show a decrease compared to the un-hot-rolled sample. Among the tested samples, the sample at 140℃-0.1MPa-10m / min had the highest average dust holding capacity, at 141.59±9.65g / m², an increase of 11.62% compared to the un-hot-rolled sample. The trends in filtration resistance for each group are shown below. Figure 5 .
[0087] When used in combination with water-electret meltblown fabric, the dust holding capacity of single-sided hot-rolled electrostatic cotton is further enhanced. Under the parameter screening condition of 85L / min, 140℃-0.05MPa-10m / min is the optimal hot-rolling parameter for the composite application scenario, with a dust holding capacity increase of 14.99% compared to the non-hot-rolled composite filter material. Multi-airflow verification further shows that the hot-rolled composite filter material prepared with this optimal parameter maintains its dust holding advantage at equivalent test airflows of 60, 85, 120, and 180L / min, with improvements of 4.29%, 14.99%, 15.75%, and 10.32%, respectively, with the largest improvement at 120L / min.
[0088] It is worth noting that, compared with using electrostatic cotton alone, the preferred hot-rolling pressure after composite meltblown fabric is reduced from 0.1 MPa to 0.05 MPa, while the preferred hot-rolling speed remains at 10 m / min; in the tested samples, the preferred hot-rolling temperature for both application scenarios is 140℃. This is because the composite meltblown fabric undertakes more of the function of intercepting fine particles, while the electrostatic cotton mainly intercepts large particles and allows some fine particles to penetrate to the meltblown fabric layer. Therefore, a lower pressure is required to maintain the relatively loose overall structure of the electrostatic cotton, while forming a thinner hot-rolled layer at 140℃ to enhance structural stability and dust holding capacity.
[0089] This invention utilizes a one-step hot rolling process to construct a gradient pore structure in electrostatic cotton. The process is simple, low-cost, and requires no chemical additives. The prepared single-sided hot-rolled electrostatic cotton and its composite filter materials not only improve dust holding capacity and slow down resistance growth, but also exhibit stable performance improvements under different filtration airflow rates, making them suitable for various indoor and outdoor air filtration scenarios.
[0090] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A single sided hot rolled electrostatic cotton for air filtration comprising an electret nonwoven substrate, characterized in that, The electret nonwoven substrate has only one side that has been hot-rolled to form a hot-rolled surface. The bulkiness of the electret nonwoven substrate decreases from the unhot-rolled surface to the hot-rolled surface. The unhot-rolled surface serves as the dust-facing surface.
2. The single-sided hot-rolled electrostatic cotton as described in claim 1, characterized in that, The parameters for hot rolling are: hot rolling temperature of 130-145℃, hot rolling linear pressure of 0.05-0.2MPa, and hot rolling speed of 6-12m / min.
3. The single-sided hot-rolled electrostatic cotton as described in claim 1, characterized in that, The fibers in the hot-rolled surface are in a flat or melt-crosslinked state, and the pores of the hot-rolled surface are not completely closed.
4. The single-sided hot-rolled electrostatic cotton as described in claim 1, characterized in that, The fiber material of the electret nonwoven substrate is selected from one or more of polypropylene, polyester, or core-sheath composite fibers; the electret nonwoven substrate is an electrostatic electret needle-punched nonwoven material.
5. A composite filter material, characterized in that, It includes the single-sided hot-rolled electrostatic cotton as described in claim 1, and a high-efficiency filter layer adhered to the hot-rolled surface of the single-sided hot-rolled electrostatic cotton.
6. The composite filter material as described in claim 5, characterized in that, The high-efficiency filter layer is selected from any one of water electret meltblown nonwoven fabric, corona electret meltblown nonwoven fabric, or glass fiber filter paper.
7. A method for preparing single-sided hot-rolled electrostatic cotton as described in any one of claims 1-4, characterized in that, The process includes a step of hot rolling an electret nonwoven substrate on one side using a light roller without a rolling point; the hot rolling temperature of the single-sided hot rolling process is 130-145℃, the hot rolling pressure is 0.05-0.2MPa, and the hot rolling speed is 6-12m / min.
8. A method for preparing single-sided hot-rolled electrostatic cotton as described in claim 7, characterized in that, The single-sided hot rolling temperature is 140℃, the hot rolling pressure is 0.1MPa, and the hot rolling speed is 10m / min.
9. A method for preparing a composite filter material as described in any one of claims 5-6, characterized in that, Includes the following steps, S1: Single-sided hot-rolled electrostatic cotton is obtained by hot-rolling electret nonwoven substrate on one side using a light roller without rolling points. S2: Bond the hot-rolled surface of the single-sided hot-rolled electrostatic cotton from step 1 to the high-efficiency filter layer.
10. The method for preparing the composite filter material as described in claim 9, characterized in that, In step 1, the hot rolling temperature is 140℃, the hot rolling pressure is 0.05 MPa, and the hot rolling speed is 10 m / min.
